An unusual cause of abdominal pain - B. Feret, Wiktoria; Gaweł, Katarzyna; Krynicka, Patrycja; Starzyńska, Teresa; Marlicz, Wojciech; Poncyljusz, Wojciech (Gastroenterology Review/Przegląd Gastroenterologiczny, 2022)
A 42-year-old woman was referred to the Gastroenterology Department because of colic, epigastric pain lasting over 3 months, with moderate improvement after analgesics/spasmolytics. She denied any other ailments. Abdominal ultrasound revealed a well-defined (42 × 32 mm) lesion, mostly solid with cystic components, near the gallbladder. Gastroscopy showed a subepithelial tumour at the posterior gastric wall of the prepyloric region, covered with normal mucosa (Figure 1 A).